Political Dialogue as Room for Verbal Aggression - SVOBODOVÁ, Jindříška (Bohemistyka, 2020)
The author analyses two specific communicative events within the political discourse in the current work. The analysis involves a dialogue between two politicians who meet face to face in a TV studio and the subsequent communication taking place on the Internet after the dialogue was made public. The utilization of offensive communicative strategies is a typical feature in political media communication where a communicating party attacks the communication counterpart with the intention of challenging his/her positive face and emphasizing his/her negative character traits in front of potential voters, while at the same time emphasizing his/her own positive values. For this reason, the author analyses the individual strategies employed by politicians with this intention in a particular communicative event. The work provides an entire chapter dealing with strategies used by participants in an Internet discussion. In this case, the communication takes place among speakers who do not know each other, so the aim of the work is to investigate whether attacks against one’s face take place even in this kind of communication, and if so, what personality traits of the communicants are attacked.